KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KUALITAS PELAYANAN DI KANTOR BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN KAMPAR - Sri Rusniawati; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Organizational communication is a process that determines the direction of the organization, the occurrence of relationships between members increases good collaboration so that goals are achieved. The pattern of organizational communication is a relationship between two or more people in the process of sending and receiving the right way so that the intended message can be understood. The fact that occurs in the BAZNAS Office is the lack of adequate quality human resources such as lack of responsiveness and ineffective communication flow resulting in misunderstandings between leaders and employees, therefore organizational communication patterns are needed in coordinating service activities in order to produce a good communication process so that the goals of BAZNAS can be achieved. The purpose of this study was to determine organizational communication, communication patterns used, and supporting factors as well as inhibiting factors in the communication process that occurs in the Kampar District BAZNAS Office. This study used qualitative research methods. The subjects of this study were the Head of BAZNAS, Head of Collection Section, Head of Distribution Section, Head of Human and General Resources Section, Field Surveyors and Human and General Resources Staff who were selected using a purposive technique. Data collection techniques consist of observation, interviews, and documentation. While the data analysis technique uses interactive analysis according to Miles and Hubermen. The data validity technique used in this study is the triangulation technique. The results of this study indicate that organizational communication patterns in improving service quality at the BAZNAS Office use the Roda pattern, the Chain pattern and the Y pattern. The Wheel pattern is used when conveying orders and controlling each member of the organization directly or via whatsapp media, the information conveyed is related to constraints and requesting solution when there is an urgent matter. The Chain Communication Pattern, namely BAZNAS employees who want to interact with the leadership must go through the heads of their respective sections because the dissemination of information on the chain pattern is formal and gradual in the form of proposals and conveyed through internal leadership meetings. In pattern Y, the information conveyed is related to official information, such as meeting schedules using invitation letters, delivery of information related to overtime work and other general information according to directions from the highest leadership. At the BAZNAS Office the supporting factors are (1) Good personal relationships, (2) Situations and Conditions, (3) Communication Media, (4) Facilities. As well as the inhibiting factors are (1) hierarchy within the organization, (2) technical barriers, (3) human barriers.